ANALYZING THE EFFECTIVENESS OF EMPLOYEE EMPOWERMENT PRACTICE ON EMPLOYEE WORK ATTITUDE STUDY CASE ON MANADO QUALITY HOTEL - Devina, Fitriyantama .; Tielung, Maria V.J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract:The sustainability of the company's business cannot be separated from the role of the employees. The organization can survive and exist, not only because of the leader or manager’s role within a company. Employee plays a very important role to make it happen. The employees’ role within an organization is in a form of their involvement in planning and process in order to achieve the organization’s objective. The purpose of this research is to analyze the effect of employee empowerment on employees’ work attitude. This research used quantitaitve method. The sample of this research is 150 respondents. This research used purposive sampling and the date filled by the questionaire. The result of this research shows that the independent variable which are social-structural empowerment and psychological empowerment simultaneously affect employee work attitude as the dependent variable, social structural empowerment as one of independent variables does not partially affects employee work attitude significantly and psychological empowerment as one of independent variables does not partially affects employee work attitude significantly.Quality Hotel Manado should enhance employee empowerment both social structural and psychological to even more because the effectiveness of empowerment towards work attitude so the performance of the company can be more improving. Keywords: employee empowerment practice